Analyzing the Impact of Transformational Leadership on Organizational Citizenship Behavior and Employee Satisfaction: The Mediating Role of “Tamoon” Relationships in the Qatari Work Environment - Al-Nuaimi, Fatima (Journal of Cultural Analysis and Social Change, 2025)
This research aims to analyze the impact of transformational leadership on organizational citizenship behavior (OCB) and employee job satisfaction, with a focus on the mediating role of the “Tamoon” relationship—a socio-cultural concept rooted in mutual trust, support, and personal interaction within Arab environments. “Tamoon” represents a key cultural factor believed to enhance the quality of leader–employee relationships, potentially reflecting positively on employees’ proactive behaviors and their overall job satisfaction. The importance of this research lies in the need to integrate local cultural values with modern leadership approaches to strike a balance between organizational governance requirements and the nature of social relations within Qatari institutions. The study aims to provide a scientific framework that enables institutions to enhance performance through culturally grounded leadership and voluntary employee engagement. The research employed a descriptive-analytical approach, utilizing a quantitative method. Data were collected through a closed-ended questionnaire based on a five-point Likert scale. The target population consisted of employees from both public and private Qatari institutions with at least two years of experience. The sample size was determined using the Krejcie and Morgan formula to ensure accurate representation of the study population. Data were analyzed using descriptive and inferential statistical tools such as correlation, regression, and path analysis to identify direct and indirect relationships among the independent variable (transformational leadership), the mediating variable (“Tamoon” relationship), and the dependent variables (organizational citizenship behavior and employee job satisfaction). The results revealed a positive impact of transformational leadership on both organizational citizenship behavior and job satisfaction, with “Tamoon” relationships reinforcing this impact through their mediating role. The research recommends developing a practical model for Qatari institutional leaders that balances the use of cultural values, such as “Tamoon,” with modern leadership practices. It also emphasizes leveraging employees’ years of experience to mentor less experienced staff, strengthening employees’ organizational attachment, analyzing gender-based differences in transformational leadership and “Tamoon” relationships, exploring variations between public and private sectors, and enhancing transformational leadership competencies.